Valorization of Date By-Products: Enhancement of Antioxidant and Antimicrobial Potentials through Fermentation - Azin Khosravi; Seyed Hadi Razavi; Ines Castangia; Maria Letizia Manca (MDPI AG, 2024)
The by-products from three varieties of dates-Mozafati, Sayer, and Kabkab-were subjected to solid-state fermentation using Aspergillus niger alone or in co-culture with Lactiplantibacillus plantarum or Limosilactobacillus reuteri to enhance their phenolic and flavonoid content, along with antioxidant and antimicrobial activities. Solid-state fermentation, being environmentally friendly and cost-effective, is particularly suitable for agricultural residues. Significant increases (p < 0.05) in total polyphenol content (TPC), total flavonoid content (TFC), and antioxidant power were observed post-fermentation, especially under co-culture conditions. The highest TPC (12.98 ± 0.29 mg GA/g) and TFC (1.83 ± 0.07 mg QE/g) were recorded in the co-culture fermentation of by-products from the Mozafati and Sayer varieties, respectively. HPLC analysis revealed changes in polyphenol profiles post-fermentation, with reductions in gallic and ferulic acids and increases in caffeic acid, p-coumaric acid, rutin, quercetin, and kaempferol. FT-IR analysis confirmed significant alterations in polyphenolic functional groups. Enhanced antimicrobial activity was also observed, with inhibition zones ranging from 8.26 ± 0.06 mm for Kabkab to 17.73 ± 0.09 mm for Mozafati. These results suggest that co-culture solid-state fermentation is a promising strategy for valorizing date by-products, with potential applications in nutraceuticals and/or pharmaceutical products and as valuable additives in the food industry.